Seasonal Patterns of Fat Deposits in Relation to Migratory Strategy in Facultative Migrants - Cornelius, Jamie M.; Hahn, Thomas P.; Robart, Ashley R.; Vernasco, Ben J.; Zahor, Dorothy L.; Glynn, Kenneth J.; Navis, Corrie J.; Watts, Heather E. (Frontiers in Ecology and Evolution, 2021)
Physiological preparations for migration generally reflect migratory strategy. Migrant birds fuel long-distance flight primarily with lipids, but carrying excess fuel is costly; thus, the amount of fat deposited prior to departure often reflects the anticipated flight duration or distance between refueling bouts. Seasonal pre-migratory deposition of fat is well documented in regular seasonal migrants, but is less described for more facultative species. We analyze fat deposits of free-living birds across several taxa of facultative migrants in the songbird subfamily Carduelinae, including house finches (Haemorhous mexicanus), American goldfinches (Spinus tristis), pine siskins (Spinus pinus) and four different North American ecotypes of red crossbills (Loxia curvirostra), to evaluate seasonal fat deposition during facultative migratory periods. Our data suggest that the extent of seasonal fat deposits corresponds with migratory tendency in these facultative taxa. Specifically, nomadic red crossbills with a seasonally predictable annual movement demonstrated relatively large seasonal fat deposits coincident with the migratory periods. In contrast, pine siskins, thought to be more variable in timing and initiation of nomadic movements, had smaller peaks in fat deposits during the migratory season, and the partial migrant American goldfinch and the resident house finch showed no peaks coincident with migratory periods. Within the red crossbills, those ecotypes that are closely associated with pine habitats showed larger peaks in fat deposits coincident with autumn migratory periods and had higher wing loading, whereas those ecotypes associated with spruces, Douglas-fir and hemlocks showed larger peaks coincident with spring migratory periods and lower wing loading. We conclude that population averages of fat deposits do reflect facultative migration strategies in these species, as well as the winter thermogenic challenges at the study locations. A difference in seasonal fattening and wing loading among red crossbill ecotypes is consistent with the possibility that they differ in their migratory biology, and we discuss these differences in light of crossbill reproductive schedules and phenologies of different conifer species.